A revision of the genus Episyron (Hymenoptera: Pompilidae) in Korea - Kim, Jeong-Kyu (Journal of Asia-Pacific biodiversity, 2023)
A revision of the genus Episyron Schiødte in Korea is presented. Three nominal species are included: Episyron arrogans (Smith), E. candiotum Whais, and E. rufipes (Linnaeus). Episyron rufipes is recorded for the first time in Korea. One of Korean species, Episyron capitosus, is a misidentification of E. arrogans. A determination key to species complemented with selective digital images is made.